Study of vertical transmission of COVID-19 infection in COVID-19 positive obstetrical patients by comparing amniotic fluid and immediate neonatal COVID-19 RT-PCR - Tyagi, Smita; Agarwal, Rajesh Kumar; Agrawal, Manish; Kapoor, Manika; Tiwari, Sakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The objective of this study was to estimate the incidence of vertical transmission COVID-19 by RT-PCR. Methods: In this hospital based prospective study, all COVID-19 positive pregnant women admitted in COVID ward in Muzaffarnagar medical college and hospital from April 2020 to January 2021 were included. A detailed history and examination was done and all routine investigations were done as per protocol. Samples were taken from amniotic fluid during vaginal delivery or caesarean section and collected in viral transport medium. Sample were also collected as nasal and oropharyngeal swab from neonate immediately after birth and sent for COVID 19 RT-PCR. Results: Out of total 50 cases; 43 (86%) neonates were delivered via LSCS and 7 (14%) by normal delivery, out of these 41 (82%) neonates were normal; 4 (8%) were IUGR, 2 (4%) were IUD, 2 (4%) were pre-term and 1 (2%) neonatal death. All 50 amniotic fluid as well as nasal and oropharyngeal samples of all neonates were negative by RT-PCR. Conclusions: Low vertical transmission may be due to the fact that antibodies are produced by mother that crosses the placenta and saves the fetus or there are highly specific immunological mediators in the placenta that do not allow the infection to pass to the fetus.